Lowest nocturnal systolic blood pressure is related to heavy proteinuria and outcomes in elderly patients with chronic kidney disease - Xinru Guo (Nature Portfolio, 2021)
Abstract Ambulatory blood pressure monitoring (ABPM) can produce many variables, of which the lowest nocturnal systolic blood pressure (LNSBP) currently used in calculating morning surge is occasionally overlooked in recent kidney studies compared with other ABPM parameters. We explored the clinical effects of LNSBP in elderly patients with chronic kidney disease (CKD) in a multicenter, observational cohort study. A total of 356 elderly patients with CKD from 19 clinics were included in this analysis. We used multiple logistic regression and survival analyses to assess the associations between the lowest nocturnal systolic blood pressure and heavy proteinuria and kidney disease outcomes, respectively. The median age was 66 years, and 66.6% were men. The median eGFR was 49.2 ml/min/1.73 m2. Multivariate logistic regression analysis demonstrated that LNSBP (OR 1.24; 95% CI 1.10–1.39; P < 0.001; per 10 mmHg) was associated with heavy proteinuria. During the median follow-up of 23 months, 70 patients (19.7%) had a composite outcome; of these, 25 initiated dialysis, 25 had 40% eGFR loss, and 20 died. Cox analysis showed that the renal risk of LNSBP for CKD outcomes remained significant even after adjusting for background factors, including age, sex, medical history of hypertension and diabetes, smoking status, eGFR, 24-h proteinuria, and etiology of CKD (HR 1.18; 95% CI 1.06–1.32; P = 0.002; per 10 mmHg). Concentrating on LNSBP could be valuable in guiding antihypertensive treatment to control heavy proteinuria and improve renal prognosis in elderly CKD patients.